The Effects of Sleep Deprivation on Mental and Physical Health - Akram, Muhammad; Umaru, Isaac John; Aslam, Nosheen; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Rashid, Abid; Al-Musawi, Jehan Mohammed; Mahmood, Abid (Kwaghe International Journal of Sciences and Technology, 2025)
Sleep is a complex, restorative, and multi-stage process essential for maintaining physical health, emotional regulation, and cognitive functioning. Beyond mere rest, sleep supports vital biological functions that sustain overall well-being. However, in today’s fast-paced society, social interactions, work demands, and excessive screen time frequently take precedence over adequate sleep, leading to widespread sleep deficiency. This phenomenon, commonly referred to as sleep deprivation, is increasingly prevalent, particularly in developing countries where technological advancement, occupational pressures, and lifestyle factors disrupt natural sleep-wake cycles. This article examines the causes and consequences of insufficient sleep, exploring the underlying biological mechanisms and their impact on cardiovascular health, immune system function, mental health, memory, and quality of life. Additionally, it underscores the importance of proper sleep hygiene and presents strategies to improve sleep patterns across all age groups, aiming to mitigate the adverse effects of sleep loss and promote holistic health.